Less Invasive Surfactant Administration Versus Intubation for Surfactant Delivery in Very Low Birth Weight Infants - Sezgin Güneş; Suzan Şahin (Galenos Yayinevi, 2022)
Aim:Routes for surfactant administration for respiratory distress syndrome (RDS) has changed from bolus endotracheal administration together with ongoing mechanical ventilation, to intubation-surfactant administration and rapid extubation (INSURE) method and finally to less invasive surfactant administration (LISA). In this study our aim was to compare respiratory outcomes of LISA and INSURE methods for surfactant delivery in very low birth weight (VLBW) infants.Materials and Methods:This retrospective, single-center study was performed in a one year period in between March 2014-2015. Data of VLBW infants who had diagnosis of RDS and received surfactant treatment via LISA or INSURE techniques were analyzed. Primary outcome of the study was failure of non-invasive respiratory support. Secondary outcomes were bronchopulmonary dysplasia diagnosis and its severity, duration of mechanical ventilation via endotracheal tube, total number of surfactant administered, duration of hospitalization and duration of all sorts of non-invasive respiratory support. Non-invasive ventilatory support failure incidences of LISA group according to gestational ages were also analyzed.Results:Fifty-nine VLBW infants in LISA group and 55 VLBW infants in INSURE group were analyzed. Need for intubation/reintubation (non-invasive ventilatory support failure) was significantly lower in LISA group (31.6% vs 49%, p=0.043). Duration of intubation was significantly longer in INSURE group [0 vs 4 days (median), p=0.001]. Both LISA and INSURE treated infants had similar moderate to severe BPD ratios (26.6% vs 32.7%, p=0.306). We did not observe any reported complications during application of both methods. Intubation ratios were lowest in the group with gestational ages 28-29 weeks (25%).Conclusion:LISA technique for surfactant delivery to preterms with RDS is a safe method ending with lower rates of need for intubation/reintubation. Even if no difference in BPD incidences in between the two groups was observed at the 36th corrected gestational week, intubation duration of infants was significantly lower in LISA group.